Tofacitinib Reprograms Human Monocytes of IBD Patients and Healthy Controls Toward a More Regulatory Phenotype. Issue 3 (27th September 2019) - Cordes, Friederike; Lenker, Eva; Spille, Lea J; Weinhage, Toni; Bettenworth, Dominik; Kessel, Christoph; Schmidt, Hartmut H; Foell, Dirk; Varga, Georg
Abstract: Background: The inhibition of Janus kinases (JAKs) and subsequent signal transducers and activators of transcription (STATs) by tofacitinib represents a new therapeutic strategy in inflammatory bowel diseases (IBD) as clinical trials have led to approval of tofacitinib for ulcerative colitis (UC) and hint at a possible efficacy for Crohn`s disease (CD). However, the impact of tofacitinib on cellular response of monocytes, which are key players in inflammatory responses, has not been investigated so far. We aimed to analyze JAK/STAT-inhibition by tofacitinib in monocytes of IBD patients and healthy controls. Methods: Primary monocytes of IBD patients with active disease and healthy controls (n = 18) were analyzed for cytokine expression and phenotype after granulocyte macrophage colony-stimulating factor (GM-CSF)/interferon (IFN)γ-stimulation and tofacitinib pretreatment (1–1000 nM) and capacity to induce Foxp3 + -regulatory T cells (Tregs) in cocultures. In total, 20 UC patients and 21 CD patients were included. Additionally, dose-dependent inhibition of JAK/STAT-phosphorylation was analyzed in controls. Results: Pro-inflammatory costimulation with GM-CSF/IFNγ resulted in significant tumor necrosis factor (TNFα) and interleukin (IL)-6 increase, whereas IL-10 expression decreased in monocytes. Tofacitinib modulated the responses of activated monocytes toward a regulatory phenotype through reduced TNFα and IL-6 secretion and enhanced Treg induction in cocultures. However, in monocytes from active IBD patients, higher tofacitinib dosages were needed for blockade of pro-inflammatory cytokines. Tofacitinib induced stronger regulatory phenotypes in monocytes of UC patients, including more effective inhibition of pro-inflammatory pathways and better restoration of anti-inflammatory mechanisms as compared with CD-derived monocytes. Conclusion: Tofacitinib dose-dependently reprograms monocytes toward a more regulatory cell type. This beneficial effect possibly results from selective JAK/STAT-blockade by adequate tofacitinib dosage with inhibition of pro-inflammatory responses and permission of a balance-shift toward regulatory pathways. Abstract : Tofacitinib reprograms monocytes of IBD patients and healthy individuals toward a more regulatory cell type by selective JAK/STAT-blockade with inhibition of inflammatory responses and permission of regulatory pathways. Tofacitinib induces stronger regulatory phenotypes in UC compared with CD-derived monocytes.